2019
DOI: 10.3390/s19030542
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Intelligence Application for Post-Earthquake Damage Mapping in Palu, Central Sulawesi, Indonesia

Abstract: A Mw 7.4 earthquake hit Donggala County, Central Sulawesi Province, Indonesia, on 28 September 2018, triggering a tsunami and liquefaction in Palu City and Donggala. Around 2101 fatalities ensued and 68,451 houses were damaged by the earthquake. In light of this devastating event, a post-earthquake map is required to establish the first step in the evacuation and mitigation plan. In this study, remote sensing imagery from the Landsat-8 and Sentinel-2 satellites was used. Pre- and post-earthquake satellite imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 43 publications
0
38
0
1
Order By: Relevance
“…Given the ability of AI to analyze large amounts of data, scenarios to deal with potential threats could be constructed simultaneous to the detection of threats [161]. This would give decision-makers and other authorities more time to respond to threats such as natural disasters [132], house fires [123], or other incidents. Furthermore, AI can be used to assess the extent of damage caused by these events helping authorities better respond to, and mitigate any damage caused [101,132].…”
Section: Ai In the Governance Dimension Of Smart Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the ability of AI to analyze large amounts of data, scenarios to deal with potential threats could be constructed simultaneous to the detection of threats [161]. This would give decision-makers and other authorities more time to respond to threats such as natural disasters [132], house fires [123], or other incidents. Furthermore, AI can be used to assess the extent of damage caused by these events helping authorities better respond to, and mitigate any damage caused [101,132].…”
Section: Ai In the Governance Dimension Of Smart Citiesmentioning
confidence: 99%
“…Syifa et al [132] An artificial intelligence application for post-earthquake damage mapping in Palu, Central Sulawesi, Indonesia…”
Section: Governance ML Nn Dl Iotmentioning
confidence: 99%
“…Both the USGS and the gCMT (global CMT: https//:www.globalcmt.org) provided the focal mechanism solutions, which indicated that the earthquake occurred on the north section of the Palu-Koro Fault, a predominantly sinistral fault with a normal component. The event resulted in catastrophic soil liquefaction; it heavily destroyed infrastructure and dwellings, and killed around 2101 people in the central Sulawesi region [6]. Another important factor that led to such a severe disaster was the tsunami that followed the main shock.…”
Section: Introductionmentioning
confidence: 99%
“…This thing causes damage to the building, such as the collapse. This liquefaction event has been proven through history that has occurred in the world, such as the earthquake in Niigata, Japan in 1964 [4,5], and the latest earthquake and tsunami in Donggala-Palu in Central Sulawesi Province with its trigger, one of which was of the Palu-Koro fault [6,7].…”
Section: Introductionmentioning
confidence: 93%